METHOD FOR MANUFACTURING THIN FILMS OF CUBI2O4 FOR PHOTOELECTROCHEMICAL APPLICATIONS - D.S. Puzikova; M.B. Dergacheva; G.M. Khussurova (Academic Scientific Journal of Chemistry, 2020)
A method has been developed for producing thin semiconductor films of a complex copper-bismuth system (CuBi2O4) with reduced roughness and increased photoactivity. The application process is carried out under standard laboratory conditions from aqueous solutions of salts, takes advantage of centrifugation to evenly distribute the coating over the surface, is characterized by low material consumption, and allows the thin nanocrystalline layers formation with a given thickness. Polyethylene glycol (PEG) is used to improve the spraying of solution droplets over the entire surface of the CuBi2O4 film, which allows the dense uniform films deposition. Scanning electron and atomic force microscopy data demonstrate the ordering of the growth of CuBi2O4 particles (size ≈200 nm) and a 1.5-fold decrease in the roughness of the relief when polyethylene glycol is added to the solution. Micrographs show the growth of uniformly sized rounded crystallites. In a comparative analysis of the XRD diagram of the samples, an increase in the number and intensity of peaks corresponding to the crystalline phase of Kusachiite (CuBi2O4) with the introduction of PEG into the initial solution is observed. Based on the photoelectrochemical measurements results, it was found that the addition of polyethylene glycol to the electrolyte helps to increase the photoactivity of the samples by 2 times. The obtained thin polycrystalline CuBi2O4 films are promising for use in photoelectrochemical converters